Faith Growing in Action: Implications of John Locke's Tabula Rasa Concept and Ecological Education for HKBP Sunday School Children - Frans Jaswin Manalu, Musdodi (UIN Sunan Kalijaga Yogyakarta, 2024)
This article explores the integration between John Locke's concept of tabula rasa and ecological education for Sunday School children in the Huria Kristen Batak Protestan (HKBP) Church. Titled